Numerical Modeling of Seismic Responses and Seismic Measures of Tunnel Crossing a Fault Zone: A Case Study - Lin Li; Liping Xian; Chaofan Yao; Deping Guo; Chengliang Liu (Advances in Materials Science and Engineering)
The investigation shows that Longxi Tunnel, across a fault zone, was severely damaged during the 2008 Wenchuan earthquake, China. In this paper, the dynamic time history analysis method is used to study the seismic response characteristics of Longxi Tunnel and the aseismic effect of seismic measures. The interfaces of the fault are simulated by bonded interfaces. The results show that high earthquake intensity, high in situ stress, and fault zone are the main reasons for damage of Longxi Tunnel. The inconsistent motion response between the normal surrounding rocks and surrounding rocks within the fault zone resulted in the damage of Longxi Tunnel, and the maximum displacement difference reaches 50 cm. With the seismic measure by setting shake absorb layer and seismic joints, the tunnel has better performance: the maximum peak internal force of the tunnel structure is reduced by about 26% and the acceleration is reduced by 30%. Seismic measures should not only be considered within fault zones but also extend to adjacent surrounding rocks. In this study, the fault seismic measures of Longxi Tunnel should be no less than 4.0 times the tunnel diameter.